ANALISIS WACANA VAN DIJK TERHADAP PENYIMPANGAN PAHAM ISLAM - Pithaloka, Dyah; Nugraha, Ari (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2021)
This research is motivated by the desire to know the deviations of Islamic understanding in the novel Tuhan Izinkan Aku Menjadi Pelacur! Memoar Luka Seorang Muslimah using discourse analysis as the basis. This type of research conducted by researchers is descriptive qualitative research with interview data, observation and documentation. In this study, the researcher emphasizes on seeing the deviations of Islamic understanding that are conveyed through the texts contained in the novel Tuhan Izinkan Aku Menjadi Pelacur! Memoar Luka Seorang Muslimah. In this case the researcher draws Islamic understanding from three aspects, namely aspects of aqidah (faith), aspects of worship, and aspects of morals which will later be linked to deviations from Islamic understanding in this novel. The results show that in this study there are deviations in Islamic understanding that are contained in the texts of the novel Tuhan Izinkan Aku Menjadi Pelacur! Memoar Luka Seorang Muslimah, starting from the aspects of aqidah (faith), worship and morals.